(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Due to the pandemic caused by COVID-19, many families in Novaliches Quezon City have lost their livelihoods, jobs, and businesses. DepEd decided to have a learning modality called the Hybrid learning modality. Because of the hybrid learning modality, the researchers want to determine if the families in Novaliches Quezon City have a problem in terms of their expenses and needs, if each family is financially ready in Novaliches in new learning modality, and this study also aimed to determine the effects of hybrid learning modality to the budget of the families in Novaliches Quezon City. It was figured out that hybrid learning affected the respondents’ budgets in Novaliches Quezon City. Furthermore, Results showed that the budget of the families in Novaliches Quezon City does not fit their different expenses and needs. This discussion is based on our recommendations that researchers can recommend to others who will do a research study about the title effect of hybrid learning modality on the budget of the families in Novaliches Quezon City because, as you can see, this discussion has a lot of knowledge that can be used as a step by researchers.